Earthquake design for controlled structures (Fracture and Structural Integrity, 2017)
An alternative design philosophy, for structures equipped with control devices, capable to resist an expected earthquake while remaining in the elastic range, is described. The idea is that a portion of the earthquake loading is undertaken by the control system and the remaining by the structure which is designed to resist elastically. The earthquake forces assuming elastic behavior (elastic forces) and elastoplastic behavior (design forces) are first calculated according to the codes. The required control forces are calculated as the difference from elastic to design forces. The maximum value of capacity of control devices is then compared to the required control force. If the capacity of the control devices is larger than the required control force then the control devices are accepted and installed in the structure and the structure is designed according to the design forces. If the capacity is smaller than the required control force then a scale factor, ?, reducing the elastic forces to new design forces is calculated. The structure is redesigned and devices are installed. The proposed procedure ensures that the structure behaves elastically (without damage) for the expected earthquake at no additional cost, excluding that of buying and installing the control devices.
Keywords: Response spectrum analysis; Structural control; Earthquake engineering